Luminescent Thermometers: Implementing Thermometry on Silicon Surfaces Functionalized by Lanthanide‐Doped Self‐Assembled Polymer Monolayers (Adv. Funct. Mater. 2/2016). (January 2016) - Rodrigues, Mafalda; Piñol, Rafael; Antorrena, Guillermo; Brites, Carlos D. S.; Silva, Nuno J. O.; Murillo, José Luis; Cases, Rafael; Díez, Isabel; Palacio, Fernando; Torras, Núria; Plaza, José Antonio; Pérez‐García, Lluïsa; et al.
Abstract : The thermal gradients generated at submicrometer scale are the limiting factor of device integration in micro‐ and nanoelectronics. Silicon functionalized surfaces combine the benefits of electronic circuits with those of molecular probes. On page 200, L. D. Carlos, A. Millán, and co‐workers describe the first self‐assembled Tb 3+ /Eu 3+ ‐doped‐polymer‐based monolayer that acts as a ratiometric thermometer, displaying bi‐stability that can be used as an optically active molecular demultiplexer.